AN EXAMINATION OF THE RELATIONSHIP BETWEEN ATTACHMENT INSECURITY TO MOTHERS AND THE RISK OF EATING DISORDERS IN A SAMPLE OF FEMALE STUDENTS IN ALBANIAN COLLEGES - Ermira Hoxha (European Scientific Journal, ESJ, 2015)
The purpose of this study is to examine the relationship between attachment insecurity to mothers and the risk of eating disorders in a sample of female students in Albanian colleges. 812 female students were selected from three public universities, namely: University of Shkoder, University of Tirana, and University of Durres. They had a mean age of 19.26 and an SD of 0.89. These students completed a questionnaire about demographic and anthropometric data (that is age, height, and weight). They also provided information based on the scale of Eating Disorder Risk and Eating Disorder Inventory (Garner, 2004). This scale is composed of three subscales, namely: Body dissatisfaction, Drive for thinness, and Bulimia. Data on attachment insecurity to mothers was collected using the following sections of the questionnaire on relationship: Experience in Close Relationship and Relationship Structures (Fraley, Brennan & Waller, 2000). Comparisons between different attachment insecurity groups were made with respect to levels of eating disorder risk. Results revealed that girls with insecure attachments to their mothers differed from girls with secure attachments in levels of body dissatisfaction, drive for thinness, bulimia, and eating disorders risk. Correlational analysis indicated that the association between attachment insecurity and the risk of eating disorders, although significant, was not strong. Hence, it defines the need for further studies in this area.